(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to describe the application of the Team Games Tournament learning model to improve basketball learning outcomes with the theme of locomotor, non-locomotor and manipulative movements in basketball games for fifth-grade students of SDN Mattoangin II Makassar. This study uses a quantitative descriptive analysis approach, namely classroom action research (CAR) which is carried out in two cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this study were 20 fifth-grade students of SDN Mattoangin II Makassar. The focus of this study is the application of the Team Games Tournament learning model to improve basketball learning outcomes with the theme of locomotor, non-locomotor and manipulative movements. Data collection techniques used in this study are observation, testing and documentation. Data analysis techniques in this study use quantitative analysis. The results of the study show a significant increase in student learning outcomes at SDN Mattoangin II Makassar in the Physical Education subject of the combination of locomotor, non-locomotor and manipulative movements in basketball games with the application of the Team Games Tournament learning model. In the pre-cycle, student learning completeness only reached 35%. After the action in cycle I, the completion rate increased to 75%. In cycle 2, the student’s learning completion rate reached 100%. This shows that the action taken has been effective in improving student learning outcomes.